The Origins of Sociable Life: Evolution After Science Studies - Hird, M. author. aut Link
XII, 202 p. 14 illus.
Keywords: This ambitious book considers social scientific topics such as identity, community, sexual difference, self, and ecology from a microbial perspective. Harnessing research and evidence from earth systems science and microbiology, and particularly focusing on symbiosis and symbiogenesis, the book argues for the development of a microontology of life.